PERAN DALIHAN NA TOLU DALAM MENINGKATKAN PENDIDIKAN IPA PADA ETNOSAINS: PERSPEKTIF FILSAFAT - Gunaria Siagian; Titis Wulandari; Lufri Lufri; Asrizai Asrizai; Hardeli Hardeli (Jurnal Muara Pendidikan, 2023)
A very basic concept in the traditional Toba Batak kinship organization is the clan. Marga is a group of people who come from the same grandfather and follow the lineage from the father which is called patrilineal. Toba Batak customs are connected by a red thread that is tied in a kinship relationship "Dalihan natolu ". This study aims to analyze multidimensional science education in the ethnoscience of Dalihan Na Tolu in the perspective of ontology, epistemology, and axiology. This study is a literature study (library research) with data sources from previous research articles on topics related to science education, science concepts, ethnoscience, and Dalihan natolu .The literature review method is by searching for Discopus literature for the 2017-2022 year using keywords or the keywords Dalihan natolu . The stages of literature are carried out in a simple manner, namely: (1) Searching and presenting literature, (2) Literacy analysis process, (3) Article preparation. The stages of literature are carried out in a simple manner, namely: (1) Searching and presenting literature, (2) Literacy analysis process, (3) Article preparation. The results of the study show that (1) the nature of learning science can be classified into three dimensions, namely science as a product, science as a process, and science as an attitude; (2) Dalihan Na Tolu Dalihan Na Tolu is a philosophy that is an integral part of the life of the Toba Batak people (3) ethnoscience Dalihan Na Tolu contains the concept of kinship and can be integrated into the concept of science such as Biology, Mathematics and Physics (4) several learning models with an ethnoscience approach can improve conceptual understanding, science process skills, conservation attitudes, and students' creative thinking abilities.